2008
DOI: 10.1038/ijo.2008.125
|View full text |Cite
|
Sign up to set email alerts
|

The additive and interactive effects of parenting style and temperament in obese youth seeking treatment

Abstract: Objective To examine maternal parenting behaviors, child temperament and their potential interactions in families of obese children and demographically similar families of nonoverweight children. Design A total of 77 obese youth (M body mass index (BMI) z-score values, zBMI = 2.4; ages 8–16, 59% female, 50% African American) and their parents were recruited from a pediatric weight management clinic and compared to 69 families of nonoverweight youth (M zBMI = − 0.03). Comparison youth were classmates of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 38 publications
2
73
0
1
Order By: Relevance
“…As self-reported surveys tend to underestimate the prevalence of mental health and chronic diseases, 20-22 more research is needed to ascertain family members' diagnostic abilities in assessing health problems among other relatives. However, similar results [3][4][5][6][7][8]11,12,14,20,[23][24][25][26][27][28][29][30] and pathophysiological pathways 7,8,[31][32][33][34][35][36][37][38] support the findings of this study.…”
Section: Strengths and Limitationssupporting
confidence: 81%
“…As self-reported surveys tend to underestimate the prevalence of mental health and chronic diseases, 20-22 more research is needed to ascertain family members' diagnostic abilities in assessing health problems among other relatives. However, similar results [3][4][5][6][7][8]11,12,14,20,[23][24][25][26][27][28][29][30] and pathophysiological pathways 7,8,[31][32][33][34][35][36][37][38] support the findings of this study.…”
Section: Strengths and Limitationssupporting
confidence: 81%
“…32 An important finding in the current study was that the risk of overweight due to child eating behaviors (emotional eating and food fussiness) might depend on a child's temperament. These two eating behaviors were found to be relevant for future study.…”
Section: Discussionmentioning
confidence: 75%
“…9 Although less research has been conducted in the health and nutrition fields in relation to general parenting, some studies have reported positive relationships between parental support and healthful weight status in children. [10][11][12] The influence of psychological control and behavioral control on a child's dietary intakes are less clear and need to be studied, especially as relating to child health outcomes in young adulthood, specifically in college.…”
Section: General Parenting Behaviorsmentioning
confidence: 99%